Error management: Implications for construction - Love, Peter; Smith, J. (Emerald, 2016)
© 2016 Emerald Group Publishing Limited.Purpose-Conventional "wisdom" in construction has placed emphasis on error prevention and is often aligned with the concept of "Zero Vision"; improvements to safety and quality have been minimal. An alternative approach is needed to ensure signifcant improvements in safety and quality; thus, this paper aims to introduce the concept of error management. Design/methodology/approach-The paper reviews the extant literature and draws upon the phenomenological research and observations experienced by the authors. Findings-It is promulgated that if quality and safety performance within projects is to improve, then construction organisations and their management need to openly acknowledge their presence so that "learning from errors" can form an integral part of an organisation's fabric. This will require the institutionalisation of error reporting and an organisational (shared) responsibility for their occurrence. Originality/value-The concept of error management has not been addressed previously in the construction literature. The authors introduce the concept and provide implications for management. The observations and experiences presented in this paper provide an initial starting point for future research to explore "how" construction organisations and projects can avoid the negative error consequences and learn to prevent them in the future.